Treatment of Refractory Adrenocortical Carcinoma with Thalidomide: Analysis of 27 Patients from the European Network for the Study of Adrenal Tumours Registry - Kroiss, Matthias; Deutschbein, Timo; Schlötelburg, Wiebke; Ronchi, Cristina Lucia; Hescot, Ségolène; Körbl, Daniela; Megerle, Felix; Beuschlein, Felix; Neu, Bruno; Quinkler, Marcus; Baudin, Eric; Hahner, Stefanie; Heidemeier, Anke; Fassnacht, Martin (Experimental and Clinical Endocrinology & Diabetes, 2019)
Objective Adrenocortical carcinoma (ACC) is a rare malignancy with a dismal prognosis. In advanced stages, tumour control by mitotane and cytotoxic chemotherapy is often temporary and salvage treatments are warranted.Methods Retrospective cohort study of participants in the prospective European Networks for the Study of Adrenal Tumours (ENSAT) registry. Main outcome measures were best response during treatment, progression-free survival (PFS), both measured according to RECIST 1.1 by two blinded radiologists, and overall survival (OS).Results Twenty-seven patients (13 males; median age 44.1 years) progressing after mitotane and a median of 4 further systemic treatments were included. Thalidomide was administered as tolerated with a starting dose of 50 mg and target dose of 200 mg /d. The median interval between treatment initiation and first imaging was 10.5 (4.4-17.5) weeks. The best response to treatment was stable disease (SD, n=2) and progressive disease (n=25), with a median PFS of 11.2 weeks and a median OS of 36.4 weeks. The first patient with SD discontinued treatment due to mild epistaxis and diarrhea after 22.3 weeks. The second patient had SD at the second treatment evaluation after 25.2 weeks and continued thalidomide but then had clinical progression and deceased after 54.3 weeks. In general, thalidomide induced only mild or moderate adverse effects (mainly fatigue and gastrointestinal complaints).Conclusion Thalidomide was overall well tolerated but resulted in disease control in only 2/27 (7.4%) patients. In the absence of predictive response markers, thalidomide should only be considered in exceptional cases as a salvage therapy in ACC.
Keywords: adrenal; adverse events; cancer; efficacy; follow-up; outcome; progression; side-effects; staging; toxicity; treatment